The Effect of Fee-Based Income, Loan-to-Deposit Ratio, and Gross Domestic Product on Return on Assets at Bank Central Asia for the 2016-2023 Period - Prajna Paramananda; Vietha Devia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
This study aims to investigate the impact of Fee-Based Income (FBI), Loan to Deposit Ratio (LDR), and Gross Domestic Product (GDP) growth on the Return on Assets (ROA) of Bank BCA between 2016 and 2023. Employing a descriptive quantitative approach, this research utilizes secondary data in the form of panel data derived from time series data. The sample comprises quarterly financial statement data of Bank Central Asia (BCA) from 2016 to 2023 and cumulative GDP growth data sourced from the Central Statistics Agency for National Statistics. The analysis reveals that FBI, LDR, and GDP collectively influence the ROA of Bank BCA during the specified period. However, when examined individually, only the Loan to Deposit Ratio (LDR) does not have a statistically significant effect on Bank BCA's ROA. Conversely, both Fee-Based Income (FBI) and GDP growth individually exert a significant influence on Bank BCA's ROA from 2016 to 2023.